1998 год. Осенняя сессия. 31 авг. - 11 сен. - Теплова М. О. (2000)
Экземпляры: КХ (20040112) / Инвентарный номер: 1049403 / Цена: 40.00 / Сис.шифр: 67.400 / Авт.знак: Г 72 / ГРНТИ: 10 / ББК: 67.400.621